Leveraging Technology for Transformative Changes : Analysing the Recommendations of the National Education Policy 2020 for the Indian School Education System - Barbhuiya, Rejaul Karim (JOURNAL OF INDIAN EDUCATION, 2023)
Education policies play a vital role in shaping the development of human capital and consequently, the overall progress of a nation. India, the world’s most populous democratic country, has introduced three significant education policies in 1968, 1986 and 2020. The National Education Policy (NEP) 2020 has reemphasised on universal access to education to attain basic literacy and numeracy skills, curtailing dropout rates and holistic development of learners. The policy advocates for extensive use of technology to enhance teaching-learning practices, address language barriers, provide personalised learning, perform continuous and holistic assessment, support teacher development, and improve educational administration. This research article explores the policy’s focus on integrating technology to address challenges in the Indian school education system. It examines NEP recommendations on digital learning resources, personalised learning paths and the integration of emerging technologies like AI, ML, Robotics, Blockchain, and Data Science into the curriculum. The use of interactive technologies such as AR, VR, and simulations to create engaging educational contents are discussed. By categorising the NEP recommendations and analysing their implications, this study sheds light on the potential impact of technology adoption in resolving challenges faced by the Indian school education system.